Self-reported Eyeglass Use by US Medicare Beneficiaries Aged 65 Years or Older - Otte, Benjamin (JAMA Ophthalmol, 2018)
IMPORTANCE: Medicare benefits do not include coverage for eyeglasses except after cataract surgery. Understanding the implications of a change to this policy would require knowing the number of Medicare beneficiaries who use eyeglasses, but no recent estimates are available. OBJECTIVE: To estimate the number of older adults with Medicare who use eyeglasses. DESIGN, SETTING, PARTICIPANTS: This cross-sectional study used data from the 2015 US National Health and Aging Trends Study. Nationally representative data from 7497 respondents were reviewed and sample weights were applied so that the data represented 43.9 million Medicare beneficiaries aged 65 years or older. The estimates were based on the following 4 groupings of beneficiaries: (1) number who used eyeglasses for distance vision correction and had distance vision impairment, (2) number who did not use eyeglasses for distance vision correction and had distance vision impairment, (3) number who used eyeglasses for near vision correction and had near vision impairment, and (4) number who did not use eyeglasses for near vision correction and had near vision impairment. The prevalence of self-reported use of glasses was estimated using the results of this survey and the Medicare enrollment file. Data were analyzed from July 12, 2017, to November 30, 2017. MAIN OUTCOMES AND MEASURES: Self-reported use of eyeglasses or contact lenses. RESULTS: Of the estimated 43.9 million Medicare beneficiaries aged 65 years or older in 2015, approximately 40.5 million (92.4%; 95% CI, 91.6%-93.1%) reported using eyeglasses for either distance or near vision correction. Differences in sociodemographics were observed between those who reported using eyeglasses. Individuals who were older, were nonwhite, had lower educational levels, were less affluent, and had prior cataract surgery were significantly less likely to use eyeglasses. Approximately 27 million beneficiaries (61.7%; 95% CI, 60.3%-63.1%) used eyeglasses for distance vision correction, and approximately 37.2 million beneficiaries (84.8%; 95% CI, 83.8%-85.8%) used eyeglasses for near vision correction. CONCLUSIONS AND RELEVANCE: Potential sociodemographic disparities in eyeglass use by age, race/ethnicity, educational level, and income were identified. This finding suggests that innovative public policy solutions are needed to address these disparities among the large number of Medicare beneficiaries who use eyeglasses.